Can Digital Transformation Foster Business Innovation: Moderating Effect based on Internationalization Openness - Huang, Yiqiong (Transactions on Economics, Business and Management Research, 2024)
Under the background of double innovation, China has vigorously promoted enterprise digital transformation. This paper takes A-share listed companies from 2012 to 2022 as a sample to empirically examine the relationship between enterprise digital transformation and enterprise innovation, and the research results show that: enterprise digital transformation can significantly and positively affect enterprise innovation; at the same time, the degree of enterprise internationalization and openness plays a positive moderating role between digital transformation and enterprise innovation; Compared with state-owned enterprises and enterprises whose executives have no overseas background, the digital transformation of non-state-owned enterprises and enterprises whose executives have overseas background has a more significant effect on enterprise innovation; this paper extends the existing research by including digital transformation and enterprise innovation in the same analytical framework, and puts forward corresponding suggestions.